Meningkatkan Hasil Belajar Pendidikan Agama Katolik Bagi Siswa Kelas VII SMPN 3 Kelam Permai Melalui Materi Peran Keluarga Bagi Perkembanganku dengan Metode Problem Based Learning Tahun Ajaran 2024/2025 - Gaderia Gaderia (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The conditions observed during Catholic Religion lessons for seventh-grade students at SMPN 3 Kelam Permai in the 2024/2025 academic year indicate a lack of concentration among students. They frequently engage in conversations with peers, exhibit limited fluency in articulating their opinions, struggle with analyzing the material being studied, and demonstrate minimal participation in class activities. These factors collectively contribute to suboptimal student learning outcomes. The problem formulation in this study is as follows: How is the Problem-Based Learning (PBL) method applied to the topic